Исследование механизмов взаимодействия низкочастотных направленных волн с несплошностями трубопроводных систем - Бондаренко, А.И. (Техническая диагностика и неразрушающий контроль, 2009)
The paper deals with the main features of excitation and regularities of propagation of low-frequency directional waves of the longitudinal and torsional modes in extended pipeline systems. The mechanisms of reflection and propagation of directional waves on the boundary of the pipe cross-section change and detection of various discontinuities in pipelines have been studied.